Isochoric thermal conductivity of solid n-alkanes:hexane C6H14 - Konstantinov, V.A.; Revyakin, V.P.; Sagan, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The isochoric thermal conductivity of solid n-hexane C6H14 has been investigated on three samples of different density in the temperature interval from 100 K to the onset of melting. In all the cases the isochoric thermal conductivity varied following a dependence which is weaker than Λ µ 1/Т. The results obtained are compared with the thermal conductivities of other representatives of n-alkanes. The contributions of low-frequency phonons and “diffuse modes” to the thermal conductivity are calculated.